Performance enhancement of CZTS-based solar cells with tungsten disulfide as a new buffer layer. (1st January 2023) - Moustafa, M.; Mourched, B.; Salem, S.; Yasin, S.
Abstract: 2D layered Transition Metal Dichalcogenide materials (TMDCs) have shown promising potential for ultra-thin photovoltaic and solar cells applications owing to their outstanding photon absorption and electrical and optoelectronics features. This paper intended to discuss a numerical exploration of the CZTS based solar cells employing the solar cell capacitance simulator (SCAPS-1D), using a novel non-toxic n -type WS2 TMDCs as a buffer layer. The cell parameters, such as the thickness and defect density of the CZTS absorber, are optimized. Then, the impact of the energy bandgap (Eg ) and the back contact work function of the WS2 buffer layer on cell performance is investigated. An optimized Eg of 2.2 eV is declared. The results refer to the promoting conduction band alignments at the interface of the buffer absorber (i.e., WS2 /CZTS). Further, we have studied the photovoltaic cell performance versus the defect level of the WS2 buffer layer. It was resolved that deep defect levels exceeding 1 × 10 18 cm −3 degrade cell efficiency. The results show an optimized power conversion efficiency of about 26.81% with Voc = 1.17 V, Jsc = 27.7 mA/cm 2, and FF = 83.66%. The simulation was further analyzed and discussed at various operating temperatures. The novel device architecture using WS2 as a buffer layer might encourage the fabrication of non-toxic CZTS solar cells. Highlights: We have described a numerical simulation of CZTS-based solar cells using the SCAPS simulator with WS2 TMDC as a novel buffer layer. The impact of the CZTS absorber layer thickness and the defect density on the photovoltaic cell parameters is studied. For the WS2 buffer layer, the effect of the energy bandgap, the defect level, the interface defect between the absorber and buffer layer, and the back contact work function values are investigated and discussed. Based on optimization, an optimized power conversion efficiency of about 26.81% has been achieved with Voc = 1.17 V, Jsc = 27.7 mA/cm 2, and FF = 83.66%. The operating temperature-dependant on the solar cell performance is discussed.